Diretrizes para o design de jogos colaborativos que incluam estudantes com Transtorno do Espectro Autista - Oresotu, Rhana Omolayo Pinheiro (Universidade Federal de São Carlos, 2025)
The number of children with Autism Spectrum Disorder (ASD) enrolled in regular Brazilian schools has significantly increased. ASD is characterized by difficulties in communication and social interaction, along with the presence of restricted and repetitive behaviors and interests. Several serious games have been developed to stimulate cognitive and social skills in people with ASD, many of which are therapeutically focused and applied in clinics. However, game design guidelines for this audience often do not consider inclusive approaches that promote collaborative learning experiences, including students with ASD. This study aims to develop a set of guidelines for designing collaborative educational games that include students with ASD. The research began with a systematic literature review to map the state of the art on the design of collaborative games specifically focused on or inclusive of people with ASD. Based on the literature review and results from Ziviani’s (2024) work on guidelines for the design of multiplayer collaborative educational games, an initial set of guidelines was developed and refined throughout the study. For the first refinements of these guidelines, a qualitative case study was conducted with a game originally designed to be collaborative, but without considering the inclusion of students with ASD. This game was applied in a municipal school with students from elementary school and high school, including students with ASD, evaluating aspects of collaboration and inclusion in the school context through direct observation, focus groups with students, and interviews with the special education expert who supervised the study. Based on the observations and suggestions collected, the first adaptation of the game was made, which was then applied in a second case study with the same students. In a focus group with special education experts, several points of uncertainty about the set of guidelines and the initial redesign of the game were discussed and refined. The study was then expanded to a third case study, in which the final version of the game, enhanced from the previous analyses, was applied to two new classes of students, including both students with and without ASD from the 6th grade of elementary school. The results demonstrated that it was possible to build a set of guidelines for designing collaborative educational games that include students with ASD. These guidelines were applied in the redesign of an inclusive collaborative game, which was used in the school context, effectively promoting interaction and collaboration among students, including those with ASD.
Guidelines for the design of collaborative games that include students with Autism Spectrum Disorder
Keywords: Transtorno do Espectro Autista; Design inclusivo; Jogos educacionais; Autism Spectrum Disorder; Inclusive design; Educational games; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO